RNF43 inhibits WNT5A-driven signaling and suppresses melanoma invasion and resistance to the targeted therapy - Radaszkiewicz, Tomasz; Nosková, Michaela; Gömöryová, Kristína; Vondálová Blanářová, Olga; Radaszkiewicz, Katarzyna Anna; Picková, Markéta; Víchová, Ráchel; Gybeľ, Tomáš; Kaiser, Karol; Demková, Lucia; Kučerová, Lucia; Bárta, Tomáš; et al. (eLife, 2021)
RNF43 is an E3 ubiquitin ligase and known negative regulator of WNT/β-catenin signaling. We demonstrate that RNF43 is also a regulator of noncanonical WNT5A-induced signaling in human cells. Analysis of the RNF43 interactome using BioID and immunoprecipitation showed that RNF43 can interact with the core receptor complex components dedicated to the noncanonical Wnt pathway such as ROR1, ROR2, VANGL1, and VANGL2. RNF43 triggers VANGL2 ubiquitination and proteasomal degradation and clathrin-dependent internalization of ROR1 receptor and inhibits ROR2 activation. These activities of RNF43 are physiologically relevant and block pro-metastatic WNT5A signaling in melanoma. RNF43 inhibits responses to WNT5A, which results in the suppression of invasive properties of melanoma cells. Furthermore, RNF43 prevented WNT5A-assisted development of resistance to BRAF V600E and MEK inhibitors. Next, RNF43 acted as melanoma suppressor and improved response to targeted therapies in vivo. In line with these findings, RNF43 expression decreases during melanoma progression and RNF43-low patients have a worse prognosis. We conclude that RNF43 is a newly discovered negative regulator of WNT5A-mediated biological responses that desensitizes cells to WNT5A.
Keywords: WNT5A; Male; signální transdukce; mouse; Neoplasm Invasiveness; RNF43; BRAF V600E; Ubiquitin-Protein Ligases; mužské pohlaví; ubikvitinligasy; Signal Transduction; protein Wnt 5a; Wnt-5a Protein; human; myši inbrední NOD; Melanoma; ROR1; cancer biology; Animals; melanoma; zvířata; invazivní růst nádoru; myši; cell biology; VANGL1; Mice; Mice, Inbred NOD; melanom